(untitled) (Bangladesh Journal of Medical Science, 2024)
The case report addresses the challenge of correcting anterior cross bite in mixed dentition period. It emphasizes the complexity of treating skeletal Class III malocclusion, especially in young patients, and highlights the importance of choosing appropriate orthodontic appliances for effective treatment. The subject of the case report is a 9-year-old girl, MK, who presented with a prognathic profile, upper and lower incisor proclination, and bimaxillary protrusion. The treatment plan was multifaceted, incorporating oral prophylaxis, fluoride application, indirect pulp capping, and strategic extractions. Key appliances used were the Quadhelix and Catalans appliances, supplemented by a lower inclined plane, removable Jack Screw appliance with a posterior bite plane, and a Nance Palatal Arch space maintainer. The report meticulously documents the treatment progression with detailed photographs and radiographs, capturing changes at 10 days, 24 days, and 3.5 months intervals. The case report concludes that the use of Quadhelix and Catalans appliances, in conjunction with a comprehensive treatment plan, effectively corrected the anterior crossbite in this patient. The treatment led to significant dental and skeletal improvements, as evidenced by the post-treatment cephalometric analysis. This case underscores the effectiveness of these appliances in pediatric orthodontic cases with similar presentations. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S43-S47